Análise comparativa da performance de elementos resistivos na soldagem por resistência elétrica em compósitos PEI/fibras de carbono - Quan, Natália Di Giuseppe [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The electrical resistance welding is already known and widely used in the process of joining sheet metal. However, composites do not conduct electrical current, making it difficult to use this method for their union. Consequently, it requires the introduction of a resistive material to promote the passage of the current in the interface to be welded. This heating element is considered a crucial part of the process for composite electric resistance and it is essential for transmitting the energy required for the welding of these materials. Since the metal mesh cannot be removed after the weld, it is considered as a contaminant, nonetheless is the foremost contributor to the quality of the joint. Therefore, the aim of this study was to comparatively evaluate the performance of two heating elements (stainless steel of different metal mesh and carbon fibers) in electrical resistance welding of composite PEI (polyétherimide) reinforced with carbon fibers. Mechanical testing (Lap shear and Iosipescu) and thermal analysis (DMA- dynamic mechanical analysis and TMA - thermomechanical analysis) were conducted together with morphological analysis of optical microscopy. In addition, composites samples produced with stainless steel metal mesh were submitted to both ultraviolet radiation chamber and hygrothermal chamber for further evaluation by the same mechanical tests, thermal and microscopic analysis. The heating element more appropriate for the electrical resistance welding of composite PEI/carbon fibers was the stainless steel of 300 metal mesh. The highest shear strength values of Iosipescu and Lap shear were obtained with this metal mesh. In general, samples submitted to hygrothermal conditioning in a climatic chamber with the stainless steel of 200 and 300 metal mesh showed lower values of glass transition temperature, coefficient of linear thermal expansion, shear and tensile strength, compared ... (Complete abstract click electronic access below)

A soldagem por resistência elétrica já é conhecida e amplamente utilizada nos processos de união de chapas metálicas. Porém, materiais compósitos poliméricos conduzem pouco a corrente elétrica, dificultando a utilização deste método para sua união. Assim, é necessária a introdução de material condutor para promover a passagem de corrente elétrica na interface a ser soldada. O elemento resistivo é considerado como o elemento crucial de todo o processo por resistência elétrica para compósitos. Por não ser possível sua remoção dos materiais unidos depois da solda, este é considerado como contaminante, porém, é o principal contribuinte para a qualidade da solda. Neste sentido, a proposta deste trabalho foi avaliar comparativamente o desempenho de dois elementos resistivos (malha metálica de diferentes mesh e tecido de fibra de carbono) na soldagem por resistência elétrica de compósitos de PEI (poli-éter-imida) com fibras de carbono. Para isto, ensaios mecânicos (lap shear e Iosipescu) e de análise térmica (DMA - análise dinâmico mecânica e TMA - análise termomecânica) foram conduzidos juntamente com ensaios morfológicos de microscopia óptica. Além disso, amostras de compósitos produzidos com a malha metálica foram submetidas tanto a condicionamento em câmara de radiação ultravioleta (UV) quanto em câmara higrotérmica para posterior avaliação pelos mesmos ensaios mecânicos, de análise térmica e microscopia. O elemento resistivo que se mostrou mais adequado para o processo de soldagem por resistência elétrica do compósito de PEI/fibra de carbono foi a malha metálica de 300 mesh. Os maiores valores de resistência ao cisalhamento Iosipescu e ao lap shear foram obtidos com esta malha metálica. Em geral, as amostras condicionadas em câmara higrotérmica com as malhas de 200 e 300 mesh apresentaram menores valores... (Resumo completo, clicar acesso eletrônico abaixo)
Comparative analysis of the performance of resistive elements in electrical resistance welding in PEI / carbon fiber composites
Keywords: Soldagem; Fibras de carbono; Compósitos poliméricos; Termoplasticos; Microscopia; Welding